Deposition and characterization of TiN-coated steels at various N 2 gas flow rates with constant etching by using capvd technique - Ali, Mubarak; Hamzah, Esah; Mohd Toff, Mohd Radzi (World Scientific, 2007)
Cathodic Arc Physical Vapor Deposition (CAPVD), a technique used for the deposition of hard coatings, for tooling applications, has many advantages. The main drawback of this technique is the formation of macrodroplets (MDs) during deposition, resulting in films with rougher morphology. Constant etching, by increasing nitrogen gas flow rate up to 200 sccm, helped in reducing the MD size and number; at higher rates, of say 300 sccm, the behavior was reversed. Minimum value of surface roughness recorded at 200 sccm was measured via both surface roughness tester and atomic force microscopy (AFM). Micro-Vickers hardness of TiN-coated tool showed about 564% times increase in hardness than the uncoated one. Scratch tester was used to study the critical loads for the coating and the excellent adhesion achievable, of say 200 sccm, was demonstrated, with relevance to the various modes.